2013
DOI: 10.1038/ncomms2824
|View full text |Cite
|
Sign up to set email alerts
|

SMRT compounds abrogate cellular phenotypes of ataxia telangiectasia in neural derivatives of patient-specific hiPSCs

Abstract: Ataxia telangiectasia is a devastating neurodegenerative disease caused primarily by loss of function mutations in ATM, a hierarchical DNA repair gene and tumour suppressor. So far, murine models of ataxia telangiectasia have failed to accurately recapitulate many aspects of the disease, most notably, the progressive cerebellar ataxia. Here we present a model of human ataxia telangiectasia using induced pluripotent stem cells, and show that small molecule read-through compounds, designed to induce read-through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 46 publications
4
24
0
Order By: Relevance
“…We were not able to detect any consistently up or downregulated genes or pathways in pluripotent state between A-T iPSCs and iPSCs generated from healthy donor fibroblasts (WT iPSCs). These data show that ATM deficiency does not affect global gene expression in the pluripotent state, similar to previous reports [21][22][23][24].…”
Section: Ipscs With Deficiencies In Atmsupporting
confidence: 92%
See 1 more Smart Citation
“…We were not able to detect any consistently up or downregulated genes or pathways in pluripotent state between A-T iPSCs and iPSCs generated from healthy donor fibroblasts (WT iPSCs). These data show that ATM deficiency does not affect global gene expression in the pluripotent state, similar to previous reports [21][22][23][24].…”
Section: Ipscs With Deficiencies In Atmsupporting
confidence: 92%
“…Mutations in ATM result in defective cell cycle checkpoint activation and a reduced capacity for repair of DNA double-strand breaks (DSBs). iPSCs from A-T patients have been generated by multiple laboratories, but the issue of genomic variation has not been comprehensively investigated [20][21][22][23][24]. We analyze the CNVs of iPSCs derived from A-T patient using high-resolution single-nucleotide polymorphism (SNP) array and discovered differential genome-wide distribution relative to replication timing organization and the effects of integrating versus nonintegrating reprogramming methods.…”
mentioning
confidence: 99%
“…Another study found that a chemical screen could identify a compound reversing the effects of the rare disease, ataxia-telangiectasia, in neural cells derived from patient iPSCs [61]. An additional benefit of modeling rare diseases with iPSCs is that the identification of the mechanisms of action in these disorders may facilitate the development of new therapeutics and the elucidation of fundamental processes such as survival and proliferation, which may be applied to other neurodegenerative diseases.…”
Section: Modeling Rare Cns Diseases With Ipscsmentioning
confidence: 99%
“…This was, to the best of our knowledge and at the time of writing the first exemplification of an iPS cell derived neuronal model of A-T. However this has recently changed [196,212].…”
Section: Discussionmentioning
confidence: 83%
“…It is becoming harder to ignore the accumulating evidence implicating mitochondria in a myriad of different neurological syndromes and ataxias [176,178]. A handful of papers provide evidence that ATM may be involved in regulating mitochondrial homeostasis [113,[194][195][196], however none propose a mechanism that may explain the involvement of mitochondria with the neurodegeneration in A-T. In addition to the role of mitochondria in providing energy for cellular respiration and balance of ROS, the mitochondria are also the second largest source of calcium buffering within the cell [197].…”
Section: Discussionmentioning
confidence: 99%